The Christmas candle - Boyle, Susan, 1961-; Matheson, Hans, 1975-; Barks, Samantha; Manville, Lesley; McCoy, Sylvester, ǂd 1943-; Lucado, Max ([Publisher not identified], 2014)
Deep in the heart of the English countryside lays the enchanting village of Gladbury. Legend has it every twenty-five years an angel visits the village candle maker and touches a single candle. Whoever lights the Christmas Candle will receive a miracle on Christmas Eve. But in 1890, at the dawn of the electric age, this centuries old legend may come to an end. When David Richmond, a progressive young minister from London arrives in Gladbury the villagers discover a new formula for miracles.